Enhancing adversarial transferability with local transformation - Yang Zhang; Jinbang Hong; Qing Bai; Haifeng Liang; Peican Zhu; Qun Song (Complex & Intelligent Systems)
Abstract Robust deep learning models have demonstrated significant applicability in real-world scenarios. The utilization of adversarial attacks plays a crucial role in assessing the robustness of these models. Among such attacks, transfer-based attacks, which leverage white-box models to generate adversarial examples, have garnered considerable attention. These transfer-based attacks have demonstrated remarkable efficiency, particularly under the black-box setting. Notably, existing transfer attacks often exploit input transformations to amplify their effectiveness. However, prevailing input transformation-based methods typically modify input images indiscriminately, overlooking regional disparities. To bolster the transferability of adversarial examples, we propose the Local Transformation Attack (LTA) based on forward class activation maps. Specifically, we first obtain future examples through accumulated momentum and compute forward class activation maps. Subsequently, we utilize these maps to identify crucial areas and apply pixel scaling for transformation. Finally, we update the adversarial examples by using the average gradient of the transformed image. Extensive experiments convincingly demonstrate the effectiveness of our proposed LTA. Compared to the current state-of-the-art attack approaches, LTA achieves an increase of 7.9% in black-box attack performance. Particularly, in the case of ensemble attacks, our method achieved an average attack success rate of 98.3%.